Poroelastic Relaxation in Thermally Cracked and Fluid‐Saturated Glass. Issue 2 (7th February 2020) - Ògúnsàmì, Abdulwaheed; Borgomano, Jan V. M.; Fortin, Jérôme; Jackson, Ian
Abstract: To test theoretical models of modulus dispersion and dissipation in fluid‐saturated rocks, we have investigated the broadband mechanical properties of four thermally cracked glass specimens of simple microstructure with complementary forced‐oscillation (0.004–100 Hz) and ultrasonic techniques (~1 MHz). Strong pressure dependence of moduli (bulk, Young's, and shear), axial strain, and ultrasonic wave speeds for dry conditions attests to essentially complete crack closure at a confining pressure of 15 MPa—consistent with ambient‐pressure crack aspect ratios ≤2 × 10 −4 . Oscillation of the confining pressure reveals bulk modulus dispersion and a corresponding dissipation peak, near 0.002 Hz only at the lowest effective pressure (2.5 MPa)—attributed to the transition with increasing frequency from the drained to saturated‐isobaric regime. The observations are consistent with Biot‐Gassmann's theory, with dispersion and dissipation adequately represented by Zener model. Above the draining frequency, axial forced‐oscillation tests show dispersion of Young's modulus and Poisson's ratio, and an associated broad dissipation peak centered near 0.3 Hz, thought to reflect local "squirt" flow and adequately modeled with a continuous distribution of relaxation times over two decades. Observations of Young's and shear moduli dispersion and dissipation from complementary flexural and torsional oscillation measurements for differential pressure ≤10 MPa provide supporting evidence of the transition with increasing frequency from the saturated‐isobaric to the saturated‐isolated regime—also probed by ultrasonic technique. These findings validate predictions from theoretical models of dispersion in cracked media and emphasize need for caution in the seismological application of laboratory ultrasonic data for cracked media. Key Points: Broadband bulk, Young's, and shear moduli dispersion and dissipation have been measured on thermally cracked glass specimens, using a combination of forced‐oscillation and ultrasonic techniques Crack aspect ratios, of mainly <2 × 10 −4, are inferred from the strong pressure dependence of axial strain, ultrasonic elastic wave speeds, and permeability for differential pressure P d < 15 MPa The mechanical properties of the water‐saturated specimens show evidence of both draining and squirt transition at the lowest differential pressures ≤5 MPa